2020
DOI: 10.1080/17441692.2020.1791212
|View full text |Cite
|
Sign up to set email alerts
|

Could attitudes toward COVID-19 in Spain render men more vulnerable than women?

Abstract: The COVID-19 pandemic affects the whole world. Spain is 5th in the world and 3rd in Europe with the largest number of diagnosed cases. Spanish citizens' attitudes are important in controlling the pandemic. This research assessed attitudes of Spaniards toward COVID-19 in two studies. One (n = 64) was conducted in a shopping centre in Madrid and another (n = 640) online. The results of both studies suggest that women in Spain have a 'more responsible' attitude toward the COVID-19 than men. Young adults (18-25 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
37
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 24 publications
(20 reference statements)
11
37
1
2
Order By: Relevance
“…Although minor differences were found between males and females, the latter have shown higher scores in most psychological variables studied. The study of differences based on the sex variable is a relevant line of research where several studies have recently been carried out in this regard (45). However, it will be necessary to carry out specific investigations in this field of study.…”
Section: Discussionmentioning
confidence: 99%
“…Although minor differences were found between males and females, the latter have shown higher scores in most psychological variables studied. The study of differences based on the sex variable is a relevant line of research where several studies have recently been carried out in this regard (45). However, it will be necessary to carry out specific investigations in this field of study.…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular background rendering male patients more susceptible to severe COVID-19 complications and death remains obscure, studies have suggested that higher ACE-2 expression, sex-immunological differences (e.g. interleukin (IL) IL-4, IL-10, and the IL-12 expression levels), lifestyle factors, as well as overall attitudes towards the COVID-19 pandemic, play pivotal roles in the observed outcomes [60] , [61] , [62] , [63] , [64] . Lastly, we identified increased intubation % to be associated with mortality, a finding that should be taken into context; only patients most in need of mechanical ventilation due to COVID-19 infection receive this.…”
Section: Discussionmentioning
confidence: 99%
“…This qualitative study contextualizes and connects a variety of factors leading to non-compliance, thereby supporting the numerous quantitative surveys that have been conducted worldwide about motives for compliances. 7,14,18,[20][21][22][23]29,33,36,39,40 This highlights why qualitative work is essential to understand how motivations affect and influence behaviors. The results can help to design policy measures during times of a pandemic that can be designed more effectively and more sensitively.…”
Section: Discussionmentioning
confidence: 99%